Pendampingan bimbingan belajar untuk meningkatkan motivasi belajar anak pada masa pandemi Covid-19 - Janati, Hind Farihah; Tohani, Entoh (Universitas Negeri Yogyakarta, 2023)
Education is one of the fields affected by the Covid-19 Pandemic. In online learning there are problems, one of which is a lack of motivation to learn. Efforts that can be made to overcome these problems can be through the work program of tutoring activities in the 2021 UNY KKN activities. KKN activities are carried out from 5 August 2021 to 23 November 2021. The implementation of this KKN is carried out through the stages of planning, implementation, evaluation and follow-up. The flagship program of this KKN activity is an educational program in the form of tutoring assistance to increase children's learning motivation during the Covid 19 pandemic in Kemorosari II Hamlet. The aim of this activity is to foster motivation to learn, help parents who cannot accompany their children in participating in online learning, and help children do school assignments enthusiastically and correctly during the Covid 19 pandemic. The target of this activity is school students both at elementary to middle school levels live in Kemorosari II Hamlet. Activities are carried out face to face in accordance with health protocols. As a result of this activity, children felt helped by the tutoring program and showed an enthusiastic attitude and were more motivated in learning.